2007
DOI: 10.1007/s00464-007-9487-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic liver resection for hepatocellular carcinoma

Abstract: Laparoscopic liver resection for HCC is feasible and well tolerated. Midterm survival and recurrence rates are similar to those after laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 36 publications
9
62
0
2
Order By: Relevance
“…In line with previous published data [5,6], the present authors have already shown good operative and oncological mid-term results of LLS in patients with HCC on cirrhosis [7]. However, few studies have reported survival outcome or pattern of recurrence after LLR for HCC on cirrhosis.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In line with previous published data [5,6], the present authors have already shown good operative and oncological mid-term results of LLS in patients with HCC on cirrhosis [7]. However, few studies have reported survival outcome or pattern of recurrence after LLR for HCC on cirrhosis.…”
Section: Introductionsupporting
confidence: 80%
“…With the improvements of new technology and equipment, laparoscopic liver resection (LLR) has been progressively developed, and is now considered a safe procedure even in the management of liver tumors, if performed by experienced surgeons [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The safety and feasibility of the laparoscopic approach and its short-term benefits for HCC patients with chronic liver dysfunction have been demonstrated by several series [21][22][23][24][25][26][27][28][29][30][31] . To date, several studies have investigated the major differences between laparoscopic hepatectomy and open hepatectomy (Tables 1 and 2) [32][33][34][35][36][37][38][39] .…”
Section: Laparoscopic Hepatectomy For Hcc Patients: An Overviewmentioning
confidence: 99%
“…Benefícios específicos do acesso VL são a preservação da parede abdominal e sua circulação colateral venosa, diminuindo assim o regime de hipertensão portal no pós-operatório, menor necessidade de reposição volêmica e melhor reabsorção da ascite pela preservação peritoneal 7 . Alguns grupos têm demonstrado benefício das ressecções laparoscópicas para pequenos CHC em cirróticos, com diminuição da morbidade, em especial na ocorrência de ascite pós-operatória 3,8,11,26 . Dois estudos caso-controle compararam os resultados de ressecções hepáticas VL e abertas em pacientes cirróticos.…”
Section: Tumores Primáriosunclassified